2017
DOI: 10.1021/acsmedchemlett.6b00482
|View full text |Cite
|
Sign up to set email alerts
|

Pyrano[2,3,4-cd]indole as a Scaffold for Selective Nonbasic 5-HT6R Ligands

Abstract: In this letter, we report the synthesis of a pyrano[2,3,4-]indole chemical scaffold designed through a tandem bioisostere generation/virtual screening protocol in search of 5-HTR ligands. The discovered chemical scaffold resulted in the design of highly active basic and nonbasic 5-HTR ligands (5-HTR = 1 nM for basic compound and 5-HTR = 4 nM for its neutral analog). Additionally, molecular modeling suggested that the hydroxyl group of nonbasic ligands - forms hydrogen bonds with aspartic acid D or D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, studies on the new groups of serotonin receptor ligands emerging in time revealed that the concept of high basicity was no longer applied to all compounds active towards 5-HTRs, and a number of ligands characterized by low basicity have recently been developed [23][24][25][26][27]. The non-amine structure of ligands is important in terms of developing new drug-like compounds, as it can help in getting rid of side effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the new groups of serotonin receptor ligands emerging in time revealed that the concept of high basicity was no longer applied to all compounds active towards 5-HTRs, and a number of ligands characterized by low basicity have recently been developed [23][24][25][26][27]. The non-amine structure of ligands is important in terms of developing new drug-like compounds, as it can help in getting rid of side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The state of art in 2014 indicated that more than 40% of the 5-HT 6 R ligands include indole moieties and more than 80% sulfone ones [12]. This situation has not been significantly changed for the last 4 years [13,14,15,16]. Nevertheless, this huge structurally-similar family has provided a number of compounds with therapeutic perspectives, especially promising for antagonists as potential agents useful in therapy of Alzheimer’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Among 17 antagonists that have reached clinical trials, only one non-sulfonyl and non-indole structure (1, Figure 1) can be found [4,7,10]. The situation has not been improved during last four years, providing new active compounds among 1H-pyrrolo [3,2-c]quinolones (2) [11], N1-azinylsulfonyl-1H-indoles (3) [12], spiro[pyrrolidine-3,3 -oxindoles] (4) [13] and tricyclic pyrano [2,3,4-cd]indoles (5) [14] (Figure 1), thus indicating a strong need to extend the chemical space of 5-HT 6 R ligands. Molecules 2019, 24, x; doi: www.mdpi.com/journal/molecules Serotonin receptors 5-HT6 (5-HT6Rs) seem to be the most intriguing among the members of 5-HTRs family and also highly promising as a target for innovative therapy of CNS (central nervous system)-diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The situation has not been improved during last four years, providing new active compounds among 1Hpyrrolo [3,2-c]quinolones (2) [11], N1-azinylsulfonyl-1H-indoles (3) [12], spiro[pyrrolidine-3,3′oxindoles] (4) [13] and tricyclic pyrano [2,3,4-cd]indoles (5) [14] (Figure 1), thus indicating a strong need to extend the chemical space of 5-HT6R ligands. Predominant sulfone-and indole-containing structures of serotonin receptors 5-HT6 (5-HT6R) ligands found previously: the only one non-sulfonyl and non-indole structure in clinical trials (1) [4]; the most active 5-HT6R agents that represent the chemical families recently found in primary screenings, i.e., 1H-pyrrolo [3,2-c]quinolones (2) [11], N1-azinylsulfonyl-1H-indoles (3) [12], spiro[pyrrolidine-3,3′-oxindoles] (4) [13] and tricyclic pyrano [2,3,4-cd]indoles (5) [14]; the most advanced compounds in clinical trials towards Alzheimer's disease (AD), i.e., Idalopirdine (6), Intepirdine (7) and [15]. (5-HT 6 R) ligands found previously: the only one non-sulfonyl and non-indole structure in clinical trials (1) [4]; the most active 5-HT 6 R agents that represent the chemical families recently found in primary screenings, i.e., 1H-pyrrolo [3,2-c]quinolones (2) [11], N1-azinylsulfonyl-1H-indoles (3) [12], spiro[pyrrolidine-3,3 -oxindoles] (4) [13] and tricyclic pyrano [2,3,4-cd]indoles (5) [14]; the most advanced compounds in clinical trials towards Alzheimer's disease (AD), i.e., Idalopirdine (6), Intepirdine (7) and [15].…”
Section: Introductionmentioning
confidence: 99%